Neural fatigue due to intensive learning is reversed by a nap but not by quiet waking. Issue 1 (3rd August 2020) - Nelson, Aaron B; Ricci, Serena; Tatti, Elisa; Panday, Priya; Girau, Elisa; Lin, Jing; Thomson, Brittany O; Chen, Henry; Marshall, William; Tononi, Giulio; Cirelli, Chiara; Ghilardi, M Felice
Abstract: Do brain circuits become fatigued due to intensive neural activity or plasticity? Is sleep necessary for recovery? Well-rested subjects trained extensively in a visuo-motor rotation learning task ( ROT ) or a visuo-motor task without rotation learning ( MOT ), followed by sleep or quiet wake. High-density electroencephalography showed that ROT training led to broad increases in EEG power over a frontal cluster of electrodes, with peaks in the theta (mean ± SE : 24% ± 6%, p = 0.0013) and beta ranges (10% ± 3%, p = 0.01). These traces persisted in the spontaneous EEG (sEEG) between sessions (theta: 42% ± 8%, p = 0.0001; beta: 35% ± 7%, p = 0.002) and were accompanied by increased errors in a motor test with kinematic characteristics and neural substrates similar to ROT (81.8% ± 0.8% vs. 68.2% ± 2.3%; two-tailed paired t -test: p = 0.00001; Cohen's d = 1.58), as well as by score increases of subjective task-specific fatigue (4.00 ± 0.39 vs. 5.36 ± 0.39; p = 0.0007; Cohen's d = 0.60). Intensive practice with MOT did not affect theta sEEG or the motor test. A nap, but not quiet wake, induced a local sEEG decrease of theta power by 33% (SE: 8%, p = 0.02), renormalized test performance (70.9% ± 2.9% vs 79.1% ± 2.7%, p = 0.018, Cohen's d = 0.85), and improved learning ability in ROT (adaptation rate: 71.2 ± 1.2 vs. 73.4 ± 0.9, p = 0.024; Cohen's d = 0.60). Thus, sleep is necessary to restore plasticity-induced fatigue and performance.